2005
DOI: 10.1111/j.0013-9580.2005.13404.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chronic Epilepsy Models in Antiepileptic Drug Discovery: The Effect of Topiramate on Spontaneous Motor Seizures in Rats with Kainate‐induced Epilepsy

Abstract: These data suggest that animal models with spontaneous seizures, such as kainate- and pilocarpine-treated rats, can be used efficiently for rapid testing of AEDs with a repeated-measures, crossover protocol. Furthermore, the results indicate that this design allows both dose-effect and time-course-of-recovery studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 33 publications
10
76
1
1
Order By: Relevance
“…In addition, carisbamate reduced the frequency of action potentials generated during depolarization-induced SRF. Our results are consistent with other studies that have demonstrated antiepileptic properties of carisbamate in various in vivo models of seizures (Bialer et al, 2007;Francois et al, 2005;Grabenstatter and Dudek, 2004;Nehlig et al, 2005;Rogawski, 2006;White et al, 2006). While the exact mechanism of action of carisbamate is not known and is being actively investigated, the ability of carisbamate to inhibit depolarization-induced SRF may account in part for some of the anticonvulsant effects of carisbamate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, carisbamate reduced the frequency of action potentials generated during depolarization-induced SRF. Our results are consistent with other studies that have demonstrated antiepileptic properties of carisbamate in various in vivo models of seizures (Bialer et al, 2007;Francois et al, 2005;Grabenstatter and Dudek, 2004;Nehlig et al, 2005;Rogawski, 2006;White et al, 2006). While the exact mechanism of action of carisbamate is not known and is being actively investigated, the ability of carisbamate to inhibit depolarization-induced SRF may account in part for some of the anticonvulsant effects of carisbamate.…”
Section: Discussionsupporting
confidence: 93%
“…Carisbamate has been evaluated as a novel AED and has demonstrated antiepileptic activity in a variety of in vivo seizure models including hippocampal and corneal kindling (Bialer et al, 2007;Rogawski, 2006) and the GAERS model of absence epilepsy . It also inhibits spontaneous recurrent seizures after kainate induced epilepsy (Grabenstatter and Dudek, 2004) and delays or prevents Li-Pilocarpine (Francois et al, 2005) induced epilepsy. Carisbamate is also anticonvulsant against bicuculline and picrotoxin induced seizures and in pentylenetetrazole and maximal electroshock induced seizure models (Bialer et al, 2007;Rogawski, 2006;White et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic administration of repeated, low doses of KA, results in a pattern of hippocampal degeneration similar to that observed after a single, high dose of kainate, with improved survival, and increased percentage of animals showing spontaneous seizures [20,23,24,33]. After KA administration, during the acute phase that may last up to 10 hours, the animal presents immobility, facial clonus, sniffing, wet dog shakes, and stage III to V seizures (rated according to Racine's scale), all leading to status epilepticus (SE).…”
Section: Introductionmentioning
confidence: 71%
“…carisbamate significantly reduced the frequency of spontaneous seizures (74% reduction at 30 mg/kg, P Ͻ 0.0001). 3 Furthermore, carisbamate was more effective than topiramate in completely suppressing spontaneous recurrent seizures in a larger fraction of the rats studied (i.e., seven of eight rats completely suppressed at 30 mg/kg i.p. versus one of eight rats completely suppressed at 100 mg/kg i.p., respectively).…”
Section: Pharmacologymentioning
confidence: 86%